Acceptability of Health Care–Related Risks: A Literature Review. Issue 1 (March 2016) - Quintard, Bruno; Roberts, Tamara; Nitaro, Léa; Quenon, Jean-Luc; Michel, Philippe
Abstract : Objectives: Risk management aims at reducing risks associated with hospital care to an acceptable level, both in their frequency and their impact on health. The social acceptability of risk on the part of the general population and of the health-care professionals, faced with regular information about adverse events, is undoubtedly evolving rapidly. In contrast to risk acceptability, the concept of risk perception is of limited interest to risk managers because it does not inform on the behaviors and actions resulting from these perceptions. The aim of this work was to define the concept of social acceptability of risk through an in-depth examination of a wide-ranging and multidisciplinary literature. Methods: A 1990–2010 English and French literature review was carried out in medical, epidemiological, and human and social sciences online databases, gray literature, and books. Results: Of the 5931 references retrieved, 203 met the inclusion criteria. We identified contributions from 5 major research fields: economic, sociocognitive, psychometric, sociological/anthropological, and interactionist. When assessing risks, individuals use a variety of psychological and social processes that include their perception not only of a given risk but also of their own personal and social resources. This global perception has a direct impact on the responses and actual behavior of individuals and groups, enabling them to cope with the risk and/or manage it. Conclusions: Social acceptability includes perceptions related to risks and the stated intentions of individual behavior. This concept may therefore be relevant for defining local and national patient safety priorities.